2023
DOI: 10.1002/ags3.12688
|View full text |Cite
|
Sign up to set email alerts
|

Single‐site robotic cholecystectomy versus single‐incision laparoscopic cholecystectomy: A systematic review and meta‐analysis

Abstract: BackgroundThe possibilities of minimally invasive cholecystectomy have emerged since the beginning of single‐incision laparoscopic cholecystectomy (SILC) and single‐site robotic cholecystectomy (SSRC). This study aimed to compare the feasibility, safety, and pain scores between SSRC and SILC.MethodsThe authors searched randomized or non‐randomized controlled trials and observational studies in PubMed, EuroPMC, and ClinicalTrials.gov from April 2012 until April 2022. The authors analyzed the operation time, hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Robotic cholecystectomy has become increasingly popular in recent years due to its many potential advantages over traditional laparoscopic cholecystectomy. It offers a more precise and controlled approach, improved visualization of the surgical field [5], reduced operative blood loss [6], shorter hospital stays [7] and reduced post operative pain [8,9]. It has been shown to be safe and effective in the treatment of gallbladder disease, with low rates of complications and high patient satisfaction [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robotic cholecystectomy has become increasingly popular in recent years due to its many potential advantages over traditional laparoscopic cholecystectomy. It offers a more precise and controlled approach, improved visualization of the surgical field [5], reduced operative blood loss [6], shorter hospital stays [7] and reduced post operative pain [8,9]. It has been shown to be safe and effective in the treatment of gallbladder disease, with low rates of complications and high patient satisfaction [10].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that estimated blood loss in robotic cholecystectomy is relatively comparable to laparoscopic cholecystectomy. [6] A cohort study including 612 patients presented a moderate reduction in the estimated blood loss for robotic cholecystectomy compared to laparoscopic cholecystectomy [7].…”
Section: Reduce Blood Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of published literature had focused on the short-term and long-term outcomes of SIRC to evaluate the feasibility and safety of this novel procedure. In comparison with CMLC and SILC, SIRC had noninferior intraoperative and postoperative outcomes with similar perioperative complication rate, conversion rate, and estimated blood loss, as well as comparable hospital stay and readmission rate 70 72 . The total operative time was significantly longer for SIRC, specifically the preoperative time.…”
Section: The Research Status Of Sirasmentioning
confidence: 96%
“…Despite these benefits, patients undergoing robot-assisted laparoscopic cholecystectomy (RALC) still experience significant postoperative pain. Effective pain management in these minimally invasive surgeries is essential for enhancing recovery and reducing opioid dependence, which is associated with adverse effects and risk of dependency [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%